2011
DOI: 10.1017/s0007114511006180
|View full text |Cite
|
Sign up to set email alerts
|

A soyabean diet does not modify the activity of brown adipose tissue but alters the rate of lipolysis in the retroperitoneal white adipose tissue of male rats recovering from early-life malnutrition

Abstract: Nutritional recovery with a soyabean diet decreases body and fat weights when compared with a casein diet. We investigated whether the reduced adiposity observed in rats recovering from early-life malnutrition with a soyabean diet results from alterations in lipid metabolism in white adipose tissue (WAT) and/or brown adipose tissue (BAT). Male rats from mothers fed either 17 or 6 % protein during pregnancy and lactation were maintained on 17 % casein (CC and LC groups), 17 % soyabean (CS and LS groups) or 6 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The proportions of fat deposits were determined by the lipolysis rate, which differed depending on the previous nutritional status. However, for rats subjected to protein restriction in early life, the soybean flour diet produced low lipolysis rate, whereas for the offspring from control rats the soybean flour diet resulted in high lipolysis rate (Paiva et al, 2012). In the present study, it is reasonable to suggest that the low protein diet during lactation superimposed on intrauterine protein restriction can have protected of increase adiposity in the adulthood.…”
Section: Discussionmentioning
confidence: 53%
“…The proportions of fat deposits were determined by the lipolysis rate, which differed depending on the previous nutritional status. However, for rats subjected to protein restriction in early life, the soybean flour diet produced low lipolysis rate, whereas for the offspring from control rats the soybean flour diet resulted in high lipolysis rate (Paiva et al, 2012). In the present study, it is reasonable to suggest that the low protein diet during lactation superimposed on intrauterine protein restriction can have protected of increase adiposity in the adulthood.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, we observed that serum insulin concentrations were increased in animals reared on a soybean diet, but alterations occurred in the early steps of the hepatic insulin signal transduction pathway, indicating hepatic insulin resistance [ 23 , 24 ]. Moreover, the weight and lipid content of the white adipose tissue as well as the lipolysis rate by isoproterenol in white adipocytes were decreased in rats fed the soybean diet [ 25 ]. Thus, the aim of this study was to investigate the effects of nutritional recovery after weaning with a soybean flour diet on de novo hepatic lipogenesis and inflammation in adult rats exposed to protein restriction during intrauterine life and lactation.…”
Section: Introductionmentioning
confidence: 99%